Prenatal diagnosis of recurrent moderate skeletal dysplasias in lamin B receptors - Shen, Xueping; Li, Zhi; Pan, Xuekui; Yao, Juan; Shen, Guosong; Zhang, Su; Dong, Minyue; Fan, Lihong (Frontiers in Genetics, 2023)
Greenberg dysplasia (GRBGD; OMIM# 215140) is a rare autosomal recessive prenatal lethal skeletal dysplasia caused by biallelic pathogenic variants in the lamin B receptor (LBR) gene (Gregersen et al., 2020), also known as HEM skeletal dysplasia, is an acronym for hydrops, ectopic calcification, and moth-eaten skeletal dysplasia (Clayton et al., 2010). This retrospective study analyzed recurrent prenatal lethal skeletal dysplasia in Chinese fetuses. Fetal karyotyping and chromosomal microarray analysis (CMA) did not find any abnormality while trio whole-exome sequencing (Trio-WES) identified a homozygous variant (NM_002296.4:c.1757G>A, NP_002287.2:p. Arg586His) in exon 14 of the LBR gene in both fetuses. Mutation analysis in the parents confirmed that the c.1757G>A variation is heterozygous by sanger sequencing. In-depth bioinformatics analysis and familial co-segregation suggest that the homozygous variation in the LBR gene is responsible for this recurrence prenatal lethal skeletal dysplasia, which was diagnosed as GRBGD. Our findings provided a basis for genetic counseling and will contribute to a better understanding of the correlation between phenotype and genotype in this genetic disorder.